The Effect of Daily Walnut Consumption on Dyslipidemia - İbrahim Bashan; Mustafa Bakman (Journal of Food Quality, 2018)
The aim of this study was to investigate the effect of daily walnut consumption on dyslipidemia in dietary. Within a year, the patients who have been suggested taking walnut or not in their individual dietary were scanned retrospectively and randomized into 2 groups. The first group consists of 72 cases (only those taken on the diet program) and the second group consists of 73 cases (walnut consumption in regulated diet). Baseline blood lipid parameters and anthropometric measurements were assessed in both groups and compared with values at 3rd month. p values < 0.05 were considered statistically significant. In addition, Maras 18 walnut cultivar was analyzed to determine the fatty acid profiles by chromatographic technique. When comparing lipid parameters at baseline and at the 3rd month, total cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, and triglyceride levels significantly decreased and high-density lipoprotein cholesterol levels significantly increased. As compared with the end of 3rd month values of the groups, the reduction in total cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, triglyceride levels of the subjects group (walnut consumption in regulated diet) were significantly higher than the control group (only regulated diet). Also, there was no significant difference in increase on high-density lipoprotein cholesterol levels between the groups. The results showed that daily consumption of walnut improved blood lipid levels. However, more extensive studies are needed on therapeutic usage in dyslipidemia.